The Acceptance Design Model for Library Web Services: Enhanced Features of the UUM Web Online Public Access Catalog - Olusegun, Adebambo Hameed (2011)
Over the years, there has been a huge investment into the digital library. Online Public Access Catalog (OPAC) is a way through which the materials and information of the library can be availed but was recently viewed to be undergoing reconstruction due to the change in users’ expectation. Despite the reconstruction and the huge investment in the library web OPAC. Users are however restricted from making collections and having access to their collection which thereby limits its usefulness and acceptance. This study therefore used the general methodology for design research to determine the factors that enhance the acceptance of library web OPAC and developed a library web OPAC prototype that will enhance the acceptance of library services, increases the usefulness, ease of use and the interactivity of the library services and the users. The evaluation of the developed prototype was conducted using a Technology Acceptance Model to determine its usefulness, ease of use and its acceptance among the users.